2020
DOI: 10.1111/rode.12650
|View full text |Cite
|
Sign up to set email alerts
|

Technological complexity and economic development

Abstract: Although technological complexity seems to be a crucial determinant of economic development, it remains insufficiently explored. Relying on microinformation stored in individual patent applications and by applying the network view of countries linked to the technologies they develop, we create a global technology space and derive complexity measures that position countries in this space. We use then the measures of technological diversification and the ubiquity of technologies present in a country's technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Ultimately, authorities must devise policies that encourage technology-based, export-oriented FDI in order to satisfy the demands of the economy and establish specialized industries that are competitive in the global market. Furthermore, Nepelski and De Prato's (2020) [56] analysis showed that a country's place in the global technological sector influences its level of wealth and growth. The key channel through which it occurs is the exclusiveness and originality of a country's technology portfolio in comparison to other nations.…”
Section: Asymmetric Analysis Outcomesmentioning
confidence: 99%
“…Ultimately, authorities must devise policies that encourage technology-based, export-oriented FDI in order to satisfy the demands of the economy and establish specialized industries that are competitive in the global market. Furthermore, Nepelski and De Prato's (2020) [56] analysis showed that a country's place in the global technological sector influences its level of wealth and growth. The key channel through which it occurs is the exclusiveness and originality of a country's technology portfolio in comparison to other nations.…”
Section: Asymmetric Analysis Outcomesmentioning
confidence: 99%
“…Technological complexity is a problem facing many industries at present, which has become a powerful weapon to solve problems such as organizational decision-making and technological innovation in complex environments [49]. Digital technology presents complex features, such as openness, distribution, dynamic, self-referential, malleable, and editable [6,16,21], which provide a variety of options for enterprises to realize innovation paths [15].…”
Section: Technological Affordance and Complexitymentioning
confidence: 99%
“…Differences in diversification stem from differences in capabilities across countries, resulting in differences in subsequent processes of industrial development and learning. Industrial development and learning are inseparable (Balland & Rigby, 2017; Lall, 2000; Soete, 1985), and paths of diversification and economic activities depend on technical learning and knowledge (Feldman & Audretsch, 1999; Nepelski & De Prato, 2020). More recent studies have also pointed out that successful learning from the production experience eventually leads to innovation (Berger, 2013; Eum & Lee, 2019; Locke & Wellhausen, 2014; Pisano & Shih, 2012).…”
Section: Previous Literaturementioning
confidence: 99%